Noun Phrase Complexity in English - Berlage, Eva (Cambridge : Cambridge University Press, 2014)
This book explores noun phrase complexity in English, showing that it is best accounted for both by a linear and a hierarchical parameter: its length and its type of postmodifier(s). The study is methodologically unique in that it combines univariate and multivariate analyses in an investigation of four different syntactic variables. Drawing on more than three billion words of British and American data, Eva Berlage shows that the length and the structure of the NPs, along with language-external factors such as the regional variety of English, work as powerful determinants of the variation. On a theoretical level, the book reveals that the structural complexity of NPs cannot be sufficiently captured by (phrasal) node counts but that we need to incorporate the degree to which NPs are sentential. The book is designed for researchers and students interested in syntax, language variation, sociolinguistics, structural complexity and the history of English.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).